METACOGNITIVE LISTENING STRATEGY TRAINING: EXPLORING ESL PRE-UNIVERSITY STUDENTS’ METACOGNITIVE AWARENESS AND THEIR PERCEPTION (Practitioner Research, 2020)
This study examines pre-university students’ metacognitive knowledge and their perception after nine weeks of metacognitive listening strategy training. In total, 31 students were selected from four intact classes in a matriculation college located in the northern region of Malaysia. Students received 9 weeks of Metacognitive Strategy Training (MST) during their listening classes. Focus group interviews were conducted after the strategy training to elicit students’ metacognitive knowledge and their perceptions of MST. Students were divided into five groups for the focus group interviews. Thematic analysis was used to analyse the data. The responses collected from the focus group interviews were reviewed and examined several times to develop themes and subthemes. The findings reveal that students showed a considerable amount of metacognitive knowledge in terms of their role and performance, the process of second language listening, and strategies for listening as second language listeners. Students view MST as helpful and effective to improve their listening skills. Implications for teaching and learning listening in ESL classrooms were discussed.